Evaluation of the positional reproducibility of sedation versus non-sedation state in pediatric radiotherapy: a retrospective study - Lei, Zhanquan; Shi, Yuequan; Liu, Yiqun; Gao, Bo; Shao, Kongfeng; Lin, Xijin; Wu, Lizhen; Yao, Zhaojie (Frontiers in Oncology, 2024)
ObjectiveTo assess the positional reproducibility of sedated and non-sedated pediatric tumor patients during radiotherapy through a retrospective analysis of cone-beam computed tomography (CBCT) and planned computed tomography (CT) scan data.MethodsThe positional reproducibility of 40 pediatric tumor patients, aged 2 to 17 years with a median age of 4.5 years, who received radiotherapy under sedated and non-sedated states was retrospectively compared. The first CBCT images obtained during CT-based treatment planning were analyzed. The analysis encompassed six-dimensional positional changes, including vertical (Vrt), longitudinal (Lng), lateral (Lat), rotational (Rtn), pitch, and roll directions. Kolmogorov-Smirnov Z nonparametric rank-sum testing was employed to evaluate the positional deviations, considering absolute values regardless of directionality. Data were further stratified based on different fixation methods used during treatment.ResultsSedated patients exhibited significantly smaller positional deviations in Vrt, Lng, Lat, and Rtn directions in the body membrane group compared with their non-sedated counterparts (P<0.05). Similarly, sedated patients demonstrated reduced positional deviations in Vrt, Lng, Lat, Rtn, pitch and Roll directions in the head and neck group compared with non-sedated patients (P<0.05). Meanwhile, compared with vacuum bag plus body membrane fixation, the head and shoulder film fixation technique proved superior in terms of positional reproducibility during sedated treatment, specifically in Vrt, Lng, Lat, Pitch, and Roll directions (P<0.05). Similarly, compared with the alternative fixation method, the head and shoulder film fixation method showed better positional deviations in six-Dimensional directions in non-sedated patients (P<0.05).ConclusionWhile sedated radiotherapy may offer advantages in terms of positional reproducibility, the present study underscores the importance of considering non-sedated radiotherapy as a viable option for pediatric tumor patients. Non-sedated treatment not only provides effective tumor control but also mitigates the psychological trauma and long-term side effects associated with repeated sedative drug use. Future studies should further explore the optimal sedation and fixation strategies for pediatric radiotherapy.